ANALISIS EFISIENSI PASAR MODAL PADA INDEKS SAHAM SYARIAH DI BURSA EFEK INDONESIA - Samudra, Suryadi (Katalogis, 2016)
This study intends to find out The Semi-strong Form of capital market efficiency on Islamic stock index in The Indonesia Stock Exchange (BEI). This efficiency study includes response to the circulated information in the market. The sample involves companies listed on Jakarta Islamic Index and distributed dividend during December 2013 to November 2014.Technique analysis used is quantitative and apllies event study method. The study is divided into 2 periods that are: estimation period, which takes place 2Â  months berfore the event and event period takes place in 21 days (10 days prior to the event, the event day, and 10 days post the event). Test result demonstrated that dividend annouincement has information content for the potential investors. This is shown by significant abnormal return on the dividend announcement day. In addition, it also shows that Islamic Stock Index in The Indonesia Stock Exchange is on the semi-strong form of efficiency, which is reflected by the absence of investors obtaining abnormal return consictetly in a long term. This also means that the market reacts quickly to new information provided.